The role of climate in past forest loss in an ecologically important region of South Asia. (23rd March 2022) - Haughan, Alice E.; Pettorelli, Nathalie; Potts, Simon G.; Senapathi, Deepa
Abstract: Tropical forests in India have declined at an alarming rate over the past century, with extensive literature focusing on the high contributions of agricultural expansions to deforestation, while the effects of climate change have largely been overlooked. Climate change effects, such as increasing temperatures, drought and flooding, have already occurred, and are projected to worsen. Climate velocity, a metric that accounts for spatial heterogeneity in climate, can help identify contiguous areas under greater climate stress and potential climate refuges in addition to traditional temporal trends. Here, we examined the relative contribution of climate changes to forest loss within an area of India, Jammu, Kashmir, and Ladakh during the period 2001–2018, at two spatial (regional and study area) and two temporal (seasonal and annual) scales. This includes, for the first time, a characterization of climate velocity in the area. Our findings show that annual forest loss increased substantially over the 17‐year period examined (2001–2018), with the majority of forest loss occurring in the Northeast region. Decreases in temporal trends of temperature and precipitation were most associated with forest losses, but there was large spatial and seasonal variation in the relationship. In every region except the Northeast, forest losses were correlated with faster velocities of at least one climate variable but overlapping areas of high velocities were rare. Our findings indicate that climate changes have played an important role in past forest loss within the study area but likely remain secondary to other factors at present. We stress concern for climates velocities recorded reaching 97 km year −1, and highlight that understanding the different regional and seasonal relationships between climatic conditions and forest distributions will be key to effective protection of the area's remaining forests as climate change accelerates. Abstract : The effects of climate change on tropical forest loss in India have largely been overlooked. Here, we examined the relative contribution of climate changes and velocities to forest loss during 2001–2018. Decreases in temperature and precipitation were most associated with forest losses but there was large spatial and seasonal variation in the relationship. Generally, forest losses were correlated with faster velocities of at least one climate variable and overlapping areas of high velocities were rare. Our findings indicate that climate changes have played an important role in India's past forest loss, but likely remain secondary to other factors at present.